The Susceptibility to Biodegradation of Some Consolidants Used in the Restoration of Mural Paintings - Ioana Gomoiu; Roxana Cojoc; Robert Ruginescu; Simona Neagu; Mădălin Enache; Maria Dumbrăvician; Ioana Olteanu; Roxana Rădvan; Luminița Ghervase (Applied Sciences, 2022)
This study evaluated both the possible fungal metabolites involved in the degradation of the commercial consolidant known as Paraloid® B72 and the national artisanal consolidant named transparent dispersion of casein and the deteriorative potential of melanised fungi. Fungi were found to have the capacity to produce organic acids, proteases and esterases when they grow on consolidants, which can be used as nutrients. Mycelia produced by melanised fungi affected the appearance, as well as the integrity, of consolidants applied on painted experimental models and fragments of frescoes. In treatment trials with biocides (Biotin R®, Biotin T® and Preventol® RI 80), the morphology of the consolidants, as well as the vitality of the fungi, were assessed 30 days after the inoculation with melanic fungi. Direct observation, optical microscopy, colourimetry and microbiological analysis highlighted the degradation of the consolidants by fungi and their acquired resistance after biocidal treatments. Biotin R® applied by brushing on the surface of the consolidants proved to be the most effective treatment, followed by Biotin T®. Considering the overall results for both Paraloid® B72 and transparent dispersion of casein, use of Biotin R® applied by brushing is recommended for preventive conservation.